FUNGI MIKORIZA ARBUSKULA (FMA) YANG BERASOSIASI DENGAN Durio zibethinus DI KABUPATEN MANOKWARI, PAPUA BARAT, INDONESIA - Suharno Suharno; Verena Agustini; Rosye H.R. Tanjung; Supeni Sufaati (Jurnal Pemuliaan Tanaman Hutan, 2019)
Arbuscular mycorrhizal fungi (AMF) is a symbiosis between fungi and plants. This association is mutualism, AMF contributes to increased plant growth while fungi obtain energy sources from plant assimilation. The purpose of this study was to determine the association of AMF with durian plants (Durio zibethinus) in Manokwari, West Papua. The survey was conducted in 10 villages located in 4 districts known as the center for producing durian. Observation of the presence of AMF spores in the plant's rhizosphere was carried out by the wet sieving method. Furthermore, to find out the association between the two symbionts is done by observing AMF colonization in plant roots. The types of AMF found in the plant's rhizosphere are morphologically identified based on spore characteristics. The results showed that durian was associated with AMF. The percentage of AMF colonization ranged from 39.29 to 80.00%, while the number of spores was 112-336 spores per 100 grams of soil sample. Based on the spore morphological characteristics, AMF found is dominated by the genus Glomus, Scutellospora, and Acaulospora.